Analysis of an SEIRS compartmental model for tuberculosis in Quezon City from 2007 to 2011 - Chan, Lailani D. (Animo Repository, 2014)
Tire Philippines is presently a country carrying a high burden of tuberculosis, being one of the four Western Pacific countries with the highest number of tuberculosis cases. As such, it has become increasingly important to study the dynamics of the disease in a population to identify ways in which its spread can be prevented. One such way of carrying out this analysis is to fit a Susceptible-Exposed-Infectious-Removed-Susceptible (SEIRS) compartmental model to actual data. In this paper, an SEIRS stochastic discrete-time model was fitted to data from Quezon City to determine the dynamics of tuberculosis transmission. Parameter distributions given the data were also identifled. An incidence rate of about 32 per 1000 infectious individuals was obtained from these distributions. These findings lead to a better understanding of the spread of tuberculosis within the population.